'Her death is as saintly as her life'. Media representations of royal deathbeds in Belgium, 1850–1910. (2nd October 2019) - De Spiegeleer, Christoph
ABSTRACT: This paper explores the media representations of the deathbeds of Queen Louise-Marie (1850), King Leopold I (1865), Queen Marie-Henriette (1902) and King Leopold II (1909) of Belgium. Print and visual media made the dominant ideals of the 'beautiful death' and the 'good death' tangible and visible by representing the last moments of Belgian kings and queens. Whether these representations showed the royal family in a positive or a negative light depended on the degree of compliance between the final acts of the king/queen and the dominant deathbed paradigms. The historical process of mediatisation affected the public perception of these four royal deaths and changed considerably in form and scale as time passed. Romanticised illustrations and descriptions of the deathbeds of Louise-Marie and Leopold I in weekly French illustrated newsmagazines and Belgian dailies successfully projected the ideal of 'the family on the throne' for a mid-nineteenth century bourgeois readership. Regarding the Catholic model of the 'good death', the pictures and descriptions of the deathbed of Louise-Marie served as a modern version of devotional ars moriendi-literature. On the other hand, Leopold's religious sentiments during his final moments became the object of discussion and conflicting interpretations. The remarkable gap between the idealised model of the beautiful death in the bosom of the family and the lack of family affection during the last moments of Marie-Henriette and Leopold II led to mediatised scandals against the background of a growing culture of yellow journalism in the early twentieth century.